Breaking the Silence: Necrophilia in Indonesia and the Pressing Demand for Legal Reform - Tjokorda Mirah Ary Mahadnyani; I Made Wirya Darma (Jurnal Dinamika Hukum, 2025)
Necrophilia, the act of engaging in sexual activities with corpses, remains an unregulated legal and ethical issue in Indonesia. The absence of specific legal provisions creates challenges in law enforcement and societal protection. This study analyzes the legal gaps in handling necrophilia cases and proposes reforms to ensure proper criminalization and deterrence. Using a normative legal research method, this study relies on library resources, including books, journals, and legal documents. Case studies help examine the legal and social implications of necrophilia. The findings reveal that necrophilia is not explicitly regulated under the Indonesia’s Criminal Code, leading to inconsistent legal responses and unclear punitive measures. While such acts violate societal norms and laws, their legal categorization remains ambiguous. A comparative analysis of international legal frameworks highlights the need for Indonesia to strengthen its laws. Countries like the UK and the U.S. classify necrophilia as a sexual crime, ensuring stricter penalties. The absence of similar provisions in Indonesia underscores a critical gap in the country’s criminal law, requiring urgent reform. Addressing this gap will reinforce legal protections and uphold societal values regarding the dignity of the deceased. It is recommended that Indonesia incorporate specific laws against necrophilia, drawing from international best practices, to ensure comprehensive legal enforcement and deterrence.